EFFECT OF COLOUR - Tonk, Lucky (International Journal of Research -GRANTHAALAYAH, 2014)
Colours can stimulate and excite people, increase their appetite, make them feel warm or make them feel tranquil. Red simply makes you excited according to those who study chromo dynamics. Coke’s website is red – it gives you a feel of a lazy, hot summer day – just when you feel the need to drink Coke.There’s more to colours in web design than just the emotional factor. People tend to gamble more under red light conditions than under blue light. Colours have impact on performance. Red lights make people act quicker and feel more powerful, which is not always beneficial, while blue makes people think more before acting. There is a reason STOP signs are red – you need to act right away and stop the vehicle you drive, otherwise you are in danger.